Optimizing Traffic Congestion in Route Planning Using a Simple Path Algorithm - Kuswandi, Brillian Adhiyaksa; Hamami, Faqih; Fa’rifah, Riska Yanu (Syntax Corporation, 2024)
This essay examines the various learning styles that students can choose from, depending on their preferences. In the COVID-19 era, lectures have been discontinued in classrooms all across the world, but the teaching and learning process is still possible through online platforms. There are learning types with unique characteristics that like to work alone or in groups, as well as visual, auditory, tactile, and kinesthetic learning styles. While some students will adjust to the lecturers' teaching approach, it can be challenging for lecturers to accommodate each student's unique learning preferences. In order to accommodate various student learning styles, lecturers must create their instructional materials in this manner. This article's goals are to: 1) describe and classify the idea of learning styles; 2) emphasize the significance of determining the research participants' preferred learning styles; and 3) emphasize that if a lecturer's teaching style reflects the preferences of the student's preferred learning style, the student's learning outcomes will be enhanced. In this study, a survey, a mix of quantitative and qualitative approaches, as well as questionnaires, are used to gather data on the four preferred learning styles. As a consequence, the majority of participants favored the kinesthetic learning strategy in both solo and group work. In this study, a survey, a mix of quantitative and qualitative approaches, as well as questionnaires, are used to gather data on the four preferred learning styles. As a consequence, the majority of participants favored the kinesthetic learning strategy in both solo and group work.